Accounting : understanding and practice - Leiwy, Danny (London : McGraw-Hill Higher Education, 2013)
Accounting: Understanding and Practice by Danny Leiwy and Robert Perks provides a gentle introduction to the complexities of accounting.
Part One: Introduction to Financial Accounting The statement of financial position (balance sheet) and what it tells usThe income statement (profit and loss account)The development of financial reportingRatios and interpretation: a straightforward introduction How the stock market assesses company performance Cash flow statements: understanding and preparation Advanced interpretation of company and group accounts Current issues in financial reporting Bookkeeping to trial balance Trial balance to final accounts Part Two: Financial ManagementFinancing a business Management of working capital Part Three: Introduction to Management AccountingIntroduction to management accounting Investment appraisal Budgetary planning and control Absorption costing Marginal costing and decision-making Standard costing and variance analysis Online material:Chapter: Incomplete recordsAppendix: Developments in management accounting
Previous ed.: London: McGraw-Hill Higher Education, 2007.
Includes bibliographical references and index.
Keywords: Accounting